Shared decision-making with involuntary hospital patients: a qualitative study of barriers and facilitators - Domenico Giacco; Liza Mavromara; Jennifer Gamblen; Maev Conneely; Stefan Priebe (BJPsych Open, 2018)
BackgroundLast year, there were more than 63 622 involuntary admissions to psychiatric hospitals in England. One of the core principles stipulated in the code of practice for care under the Mental Health Act is involving involuntary patients in care decisions.AimsIdentifying barriers and facilitators to shared decision-making with involuntary patients.MethodFocus groups and individual interviews with patients and clinicians who have experience with involuntary hospital treatment were carried out. Data were subjected to thematic analysis.ResultsTwenty-two patients and 16 clinicians participated. Barriers identified included challenges in communication, and noisy and busy wards making one-to-one meetings difficult. Patient involvement was identified as easier if initiated early after admission and if the whole clinical team was on board. Carers' presence helped decision-making through providing additional information and comfort.ConclusionsThe barriers and facilitators identified can inform changes in the practice of involuntary care to increase patient involvement.Declaration of interestNone.